Effect of Heating on the Fatty Acid Composition and Oxidation Products of Flaxseed Oil - Zhang1, Zhen-Shan; Li2, Dong; Zhang3, Li-Xia (Asian Journal of Chemistry, 2013)
In this study, the oxidative changes of flaxseed oil at different heating temperatures were investigated. The oxidative degradation of flaxseed oil was evaluated by monitoring the peroxide value, fatty acid composition, content of conjugated dienes as absorbance at 232 nm, content of conjugated trienes as absorbance at 270 nm. Results showed that both of heating time and temperature had significant influence on the deterioration of flaxseed oil. The peroxide value, specific extinction coefficient at 232 and 270 nm were increased with the increasing of heating time at each temperature. The relative percentage of linolenic acid obviously decreased with increasing of heating time. However, the relative percentage of palmitic acid and oleic acid obviously increased with the increasing of heating time.